The Effect of High-Dose Vitamin D on Inflammatory Markers of ICU Patients with COVID-19 - Mohammad Hossein Zamanian; Zohreh Javadfar; Shima Moradi; Roghayeh Mostafaei; Ali Soroush; Sahar Cheshmeh; Akram Rahimi (International Journal of Nutrition Sciences)
Background: Vitamin D can inhibit hyper-inflammatory responses, and there are mechanistic reasons for vitamin D’s beneficial effects in COVID-19 patients. The aim of the present study was to assess how a single high dose of vitamin D can affect inflammatory markers among COVID-19 patients in critical conditions.Methods: A single center, double-blind, randomized clinical trial was conducted on 61 COVID-19 patients admitted to the intensive care units (ICUs). The intervention group received 300,000 IU vitamin D intramuscularly and identically placebo patients were monitored for one week. The levels of lactate dehydrogenase (LDH, IU/mL), C-reactive protein (CRP, mg/L), interleukin-6 (IL-6, Pg/L), lymphocytes, neutrophils, and neutrophil/lymphocyte (N/L) ratios were measured at the start and end of the study.Results: This trial included 44 patients with COVID-19 who had vitamin D deficiency at the start. After a high vitamin D dose intervention, lymphocyte level increased while LDH (IU/mL) and neutrophil levels, and N/L ratio decreased. CRP (mg/L) and IL-6 (Pg/L) levels significantly declined following intervention with a high-dose vitamin D.Conclusion: These findings suggest that high doses of vitamin D may improve inflammatory indices in COVID-19 ICU patients.